RAB7L1-Mediated Relocalization of LRRK2 to the Golgi Complex Causes Centrosomal Deficits via RAB8A - Madero-Pérez, Jesús; Fernández, Belén; Lara Ordóñez, Antonio Jesús; Fdez, Elena; Lobbestael, Evy; Baekelandt, Veerle; Hilfiker, Sabine (Frontiers in Molecular Neuroscience, 2018)
Mutations in the LRRK2 gene cause autosomal-dominant Parkinson´s disease (PD), and both LRRK2 as well as RAB7L1 have been implicated in increased susceptibility to idiopathic PD. RAB7L1 has been shown to increase membrane-association and kinase activity of LRRK2, and both seem to be mechanistically implicated in the same pathway. Another RAB protein, RAB8A, has been identified as a prominent LRRK2 kinase substrate, and our recent work demonstrates that aberrant LRRK2-mediated phosphorylation of RAB8A leads to centrosomal alterations. Here, we show that RAB7L1 recruits LRRK2 to the Golgi complex, which causes accumulation of phosphorylated RAB8A in a pericentrosomal/centrosomal location as well as centrosomal deficits identical to those observed with pathogenic LRRK2. The centrosomal alterations induced by wildtype LRRK2 in the presence of RAB7L1 depend on Golgi integrity. This is in contrast to pathogenic LRRK2 mutants, which cause centrosomal deficits independent of Golgi integrity or largely independent on RAB7L1 expression. Furthermore, centrosomal alterations in the presence of wildtype LRRK2 and RAB7L1 are at least in part mediated by aberrant LRRK2-mediated RAB8A phosphorylation, as abolished by kinase inhibitors and reduced upon knockdown of RAB8A. These results indicate that pathogenic LRRK2, as well as increased levels of RAB7L1, cause centrosomal deficits in a manner dependent on aberrant RAB8A phosphorylation and centrosomal/pericentrosomal accumulation, suggesting that centrosomal cohesion deficits may comprise a useful cellular readout for a broader spectrum of the disease.